Practical process control - Seal, A. M. (Elsevier/Butterworth Heinemann, 1998)
This book introduces process control to engineers and technicians unfamiliar with control techniques, providing an understanding of how to actually apply control in a real industrial environment. It avoids analytical treatment of the numerous statistical process control techniques to concentrate on the practical problems involved. A practical approach is taken, making it relevant in virtually all manufacturing and process industries. There is currently no information readily available to practising engineers or students that discusses the real problems and such material is long overdue.